HUBUNGAN MORAL DISENGAGMENT DENGAN CYBERBULLYING PADA REMAJA PENGGUNA MEDIA SOSIAL - Nadila Sadinda Hasibuan; Salmiyati; Yuliana Intan Lestari; Mukhlis Mukhlis (Indonesian Psychological Research, 2023)
The frequent use of social media can increase vulnerability of adolescents to cyberbullying. Moreover, adolescents often consider cyberbullying as a normal and natural phenomenon. Seeing cyberbully as normal behavior is known as moral disengagement. This study aimed to determine the relationship between moral disengagement and cyberbullying among adolescents that actively use social media and to test gender differences in moral disengagement and cyberbullying. This study used a quantitative correlational approach to determine the relationship between the two variables. Selected using a purposive sampling technique, a total of 265 adolescents who actively used smartphones and social media with an age range of 15-18 years participated in this study. They were recruited from a state high school in Pekanbaru, Riau. The  Hymel’s moral disengagement and the  Willard's cyberbullying behavior scale were used to measured moral disengagement and cyberbullying behavior, respectively. The result of linier regression analysis indicated a significant relationship between moral disengagement and cyberbullying among young social media users. Furthermore, it was found that the male adolescents significantly scored higher in moral disengagement and cyberbullying. Implication of this findings were further discussed.